2023
DOI: 10.1590/0103-8478cr20210544
|View full text |Cite
|
Sign up to set email alerts
|

Key points for the thermal comfort of water buffaloes in Eastern Amazon

Abstract: This study presented relevant aspects about the Amazonian environment and how it impacts the thermal comfort of domestic buffaloes (Bubalus bubalis) raised in the Eastern Amazon. Furthermore, strategies for monitoring and mitigating animal heat stress are presented, based on research results with the species. Although domestic buffaloes are considered adaptable animals, exposure to intense solar radiation causes thermal discomfort. This condition is expressed in biophysical indicators, in metabolic, endocrine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“…In addition, trees can become an extra source of income for landowners [ 93 ]. In a study involving buffalo, Garcia et al [ 94 ] and Brcko et al [ 3 ] pointed out that the inclusion of trees in tropical pastures promoted greater thermal comfort for the animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, trees can become an extra source of income for landowners [ 93 ]. In a study involving buffalo, Garcia et al [ 94 ] and Brcko et al [ 3 ] pointed out that the inclusion of trees in tropical pastures promoted greater thermal comfort for the animals.…”
Section: Discussionmentioning
confidence: 99%
“…Ref. [ 94 ] and Brcko et al [ 3 ], in a study with buffaloes, observed that using trees in tropical pastures promoted greater thermal comfort.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies carried out in the Amazon region have also indicated beneficial effects of shade on the physiological responses of buffaloes ( 69 75 ). In addition to seeking shade to rest and facilitate heat dissipation, buffaloes have the habit of wallowing ( 76 ). With this behavior, the animals lay on mud to favor body cooling via conduction, combined with the effects of convection caused by the wind and evaporation of the water in the mud ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to assess the ability of animals to adjust to the prevailing environmental conditions in regions with hot climates, there are methods that are classified as “adaptability measures,” as they allow verifying the ability of animals to maintain their homeothermy or dissipate heat ( 12 ). Such methods are based on the physiological variables of the animals, such as rectal temperature, respiratory rate and body surface temperature ( 13 , 14 ). The evaluation of surface temperature through infrared thermography, a non-invasive technique that allows obtaining a distance image of a specific body region, represents a valuable tool to monitor the physiologic status, welfare and the stress responses of domestic animals ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%